A retrospective study of physiotherapy management for patients with pneumonia requiring invasive ventilation in a single-center Australian ICU - Baldwin Pok Man Kwan; Anne-Marie Hill; Mercedes Elliott; Lisa van der Lee (World Scientific Publishing, 2022)
Background: Pneumonia is a frequent diagnosis for patients admitted to Australian intensive care units (ICUs) for invasive ventilation. Physiotherapists in ICU provide interventions to enhance respiratory function and physical recovery. Objective: This retrospective cohort study aimed to describe physiotherapy management of adults with pneumonia who require invasive mechanical ventilation in a single Level 3 ICU in a quaternary teaching hospital. Methods: All adults admitted with a medical diagnosis of pneumonia requiring invasive mechanical ventilation over a two-year period were included. Demographic and clinical data, including APACHE II score, ventilator-free days (VFDs) to day 28, ICU length of stay (LOS), and type and frequency of physiotherapy episodes of care delivered in ICU, were collected from electronic medical records. Correlations between VFDs to day 28 and the frequency of physiotherapy interventions delivered per subject were examined using Spearman's rho analysis. Results: From 208 records screened, 66 subjects with an ICU admission diagnosis of pneumonia, who required invasive mechanical ventilation, were included. Median (IQR) ICU LOS was 10 (5-17) days, and mortality rate was 15.2% ([Formula: see text]). The cohort had a median of 20.5 (IQR 2-25) VFDs to day 28. Community-acquired pneumonia (66.7%, [Formula: see text]) was the most frequent type of pneumonia diagnosis. There were 1110 episodes of physiotherapy care, with patients receiving a median of 13.5 (IQR 6.8-21.3) episodes during their ICU stay, with a median rate of 1.2 (IQR 1.0-1.6) episodes per day. Over 96.7% of patients with pneumonia received physiotherapy treatment during their ICU stay. Overall, physiotherapy treatments consisting only of respiratory techniques were most commonly provided (55.1%, [Formula: see text]). Airway suctioning (92.4%, [Formula: see text]), patient positioning (72.7%, [Formula: see text]) or positioning advice to nurses (77.3%, [Formula: see text]), and hyperinflation techniques (63.6%, [Formula: see text]) were among the respiratory techniques most delivered. Conclusion: This study described the current intensive care physiotherapy management in a single center for adults with pneumonia who required invasive mechanical ventilation, demonstrating that respiratory physiotherapy interventions are often provided for this ICU patient cohort. Further research is warranted to determine the efficacy of respiratory physiotherapy interventions to justify their use for ICU patients with pneumonia receiving invasive mechanical ventilation.